About the Prince Badiuzzamon in “Hayratul-Abror” (Astonishment of Nice People) - Kodirovich, Dehkonov Akramjon (International Journal of Psychosocial Rehabilitation, 2020)
This chapter deals with the advice of the Timurid prince Badiuzzaman Mirzo, which is included in the twentieth chapter of AlisherNavoi’s epic “Hayratul-Abror”. The general content of the chapters of the Hamsa epics dedicated to young Temurid princes such as Muzaffar Mirzo, Shohgarib Mirzo, Sultan Uwais Bahodir is also mentioned. Badiuzzaman Mirza's relationship with his father, the ruler of Khorasan Sultan Hussein Boykaro, is reflected in Alisher Navoi's creative legacy, the great poet's efforts to alleviate tensions between parents and children, and the extent to which these events are reflected in the poet's work. It is noted that Navoi's advice in the chapter of the epic “Hayratul-Abror” dedicated to Badiuzzaman was very important for the prince. Alisher Navoi’s efforts and devotion to the development of the state of Sultan Hussein Boykaro were also reflected in his epics and prose. The chapter also notes that Navoi's anxious remarks in his advice to Badiuzzaman took place a quarter of a century later.